Fenomena Buzzer dalam Al-Qur’an: Analisis Surah An-Nur (24): 11 dalam Tafsir Al-Alūsĭ - Minkhatul Maula Sofa (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2025)
This article aims to examine how the Qur'an views the phenomenon of buzzer behavior on social media with an analysis of the interpretation of an-Nur (24): 11 according to the interpretation of Al-Alūsĭ , Alūsĭ seeing the shift in the role of buzzers becoming dangerous if used to create or spread hoax news and hate speech that triggers disputes and divisions. This study uses a library research method. The results of this study indicate that there is no term that mentions the word buzzer in the Qur'an, but its values ​​and actions are explained in the Qur'an. Buzzer is a profession that was initially legal and has a positive impact if used in goodness such as promoting a brand so that it becomes a form of taawun or helping each other. However, if buzzers are used to express hatred, spread news that contains elements of lies, then it is not allowed. In the interpretation of Al-Alūsĭ , one of the negative behaviors of buzzers is recorded in the Qur'an, Surah An-Nur (24): 11. Al-Alūsĭ emphasizes three segments in the explanation of this verse, namely the perpetrators of spreading false news, recommendations in responding to false news and the consequences and punishments for the perpetrators of spreading false news. In this verse, the negative behavior of buzzers has similarities with a group of people who masterminded the spread of slander against Aisyah Ra among Muslims in Medina.